Oviposición y mortalidad de tuta absoluta en Lycopersicon hirsutum - Leite, G.L.D.=700 1 Picanco, M.; Azevedo, A.A.; Zurita, Y.; Marquini, F.
ilus.; 19 ref.
Keywords: LYCOPERSICON HIRSUTUM; LYCOPERSICON ESCULENTUM; GELECHIIDAE; LEPIDOPTERA; RESISTENCIA A LAS PLAGAS; OVIPOSICION; MORTALIDAD; NITROGENO; POTASIO; COSTA RICA